Modern Business Process Automation: YAWL and its Support Environment - Hofstede, A. H. M. ter (Springer, 2012)
Topics covered include: The fundamentals of business process modeling, including workflow patterns, an in-depth treatment of process flexibility, including approaches to dealing with on-the-fly changes, unexpected exceptions, and constraint-based processes, Technological aspects of a modern BPM environment, including its architecture,  process design environment, process engine, resource handler and other support services, a comparative insight into current approaches to business process modeling and execution such as BPMN, EPCs, BPEL, jBPM, OpenWFE, and Enhydra Shark, process mining, verification, integration and configuration; and case studies in health care and screen business. This book provides a comprehensive treatment of the field of Business Process Management (BPM) with a focus on Business Process Automation.